Upper and Lower Solutions for m-Point Impulsive BVP with One-Dimensional p-Laplacian - Junfang Zhao; Jianfeng Zhao; Weigao Ge (Discrete Dynamics in Nature and Society)
Upper and lower solutions theories are established for a kind of m-point impulsive boundary value problems with p-Laplacian. By using such techniques and the Schauder fixed point theorem, the existence of solutions and positive solutions is obtained. Nagumo conditions play an important role in the nonlinear term involved with the first-order derivatives.